2014
DOI: 10.1517/17460441.2014.918947
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide: looking back at its preclinical discovery

Abstract: The landscape of CRPC has changed dramatically over the last few years, as new agents with proven benefit in overall survival have been approved. Compared to the average time of 10 - 15 years for a new drug to go from pre-clinical discovery to registration, enzalutamide obtained FDA approval in < 6 years after its initial characterization. Enzalutamide, a targeted agent of the androgen-AR axis, has shown promising results in CRPC and is generally well tolerated. However, drug resistance inevitably emerges is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In treating men with CRPC, enzalutamide is a key second generation anti-androgen used widely due to its ease of administration as well as a low toxicity profile [6]. Notwithstanding, as with all second-generation androgen manipulations, resistance to enzalutamide treatment emerges inevitably with a median time of 4.8 months [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In treating men with CRPC, enzalutamide is a key second generation anti-androgen used widely due to its ease of administration as well as a low toxicity profile [6]. Notwithstanding, as with all second-generation androgen manipulations, resistance to enzalutamide treatment emerges inevitably with a median time of 4.8 months [32].…”
Section: Discussionmentioning
confidence: 99%
“…Enzalutamide is a FDA-approved second-generation androgen receptor (AR) antagonist that blocks ligand binding, nuclear translocation, DNA binding, and coactivator recruitment of ARs [6]. In multiple clinical trials, enzalutamide has been shown to prolong overall and progression-free survival, improve patient-reported quality of life, and delay the development of skeletal-related complications in men with metastatic CRPC who are chemotherapy naïve or have previously received docetaxel [79].…”
Section: Introductionmentioning
confidence: 99%
“…In treating men with CRPC, enzalutamide is a key second generation anti-androgen used widely due to its ease of administration as well as a low toxicity profile (6). Notwithstanding, as with all second-generation androgen manipulations, resistance to enzalutamide treatment emerges inevitably with a median time of 4.8 months (31).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the first generation of AR antagonists, enzalutamide lacks AR agonistic activity (for review, see Ha & Kim 2014) and, furthermore, has been reported to bind to AR with approximately eight-fold higher affinity than bicalutamide (Tran et al 2009). …”
Section: Discussionmentioning
confidence: 99%